Effect of Gilsonite Use on Storage Stability of Styrene-butadiene-styrene Modified Bitumen - Yalcın, Erkut; Çeloğlu, M. Ertuğrul; Akpolat, Mustafa; Erdoğan Yamaç, Özge; Alataş, Taner; Kök, Baha Vural; Yılmaz, Mehmet (Periodica Polytechnica Civil Engineering, 2019)
Styrene-butadiene-styrene (SBS) polymer is one of the most preferred additives to improve performance in hot mix asphalt pavements. The storage instability, in other words, the separation of a polymer-rich phase from the bitumen-rich phase in the course of storage and transportation is one of the prevalent problems in SBS modified bitumen. The present study attempted to obtain modified bitumen at the same performance level with the SBS modified bitumen, but stable with respect to the storage stability. For this purpose, both SBS and American Gilsonite (AG) were used in modified bitumen production. It was determined that modified bitumen at the same performance level was obtained with the use of 5 % SBS or 18 % AG in bitumen modification. It was also determined that the performance levels of the modified bitumen obtained with the use of 2 % SBS + 13 % AG, 3 % SBS + 10 % AG and 4 % SBS + 6 % AG were similar. Additionally, 2 %, 3 % and 4 % SBS modified bitumen were used for the assessment of storage stability properties of the SBS modified binders. These 8 different modified bitumen samples were tested for storage stability based on the EN 13399 standard. Penetration, softening point, rotational viscometer, bending beam rheometer, and dynamic shear rheometer tests were conducted on the samples. Based on all conducted tests, it was determined that more stable binders were obtained with the use of AG and SBS in terms of storage stability compared to solely SBS modified bitumen.